Diagnosing preeclampsia: how effective are blood tests?. (18th April 2012) - Waring, GJ; Allan, CL; Taylor, P; Robson, SC; Waugh, JJS
Abstract : Background: Signs and symptoms of Preeclampsia (PE) is one of the commonest reasons for referral for urgent assessment in pregnancy. PE defined as sustained BP ≥140/90 mmHg + proteinuria (PCR≥30 or ≥0.3g/24hr). NICE guidance (Hypertension in pregnancy 2010) acknowledges the lack of robust evidence to inform biochemical and haematological assessment, suggesting they do not predict progression to PE. Methods: A retrospective analysis was undertaken over a 12 month period of all pregnant women with signs or symptoms of PE who were referred for assessment at a tertiary centre. All underwent blood pressure monitoring and automated urine dipstick for protein (+/-PCR). Blood tests to assess; kidney function, electrolytes, FBC and transaminases were taken where indicated. Assessment of these biochemical measurements at the time of a final diagnosis (PE/Gestational hypertension/Gestational proteinuria) has been made to give a statistical appraisal of the effectiveness of each test as a diagnostic tool in PE. Findings: 164 women referred to the unit had bloods taken at the time of final diagnosis. Abnormal urate, creatinine, platelets and alanine-transaminase were assessed for sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and likelihood ratios (LR+ and LR-) for diagnosing PE (table ). Interpretation: Biochemical and haematological assessments perform poorly at confirming PE, however the high specificity finding is consistent with NICE in that they are beneficial as 'rule out' tests.